Zakka wool appliqué : 60+ sweetly stitched designs, useful projects for joyful living - Kim, Minki, 1973- (C&T Publishing, 2020)
"This book features charming wool felt appliqué designs that can be put to beautiful use in projects for your home and gifting. The book has instructions for 60+ appliqué patterns, instructions for 6 projects, and a gallery of additional project ideas"--